Effectiveness of Inactivated Coronavirus Disease 2019 Vaccine Against Omicron BA.2.2 Infection in Beijing, China, 2022: A Cohabitation Retrospective Cohort Study - Shuaibing Dong; Ying Sun; Zhaomin Feng; Yi Tian; Lei Jia; Xiaoli Wang; Quanyi Wang; Daitao Zhang; Peng Yang (Viruses)
The present study aimed to evaluate the vaccine effectiveness (VE) of different doses of an inactivated coronavirus disease 2019 (COVID-19) vaccine against Omicron BA.2.2 infection in Beijing, China, 2022. Based on data from a previous cohabitation retrospective cohort of COVID-19 outbreak in Beijing, China, 2022, the cohabitating contacts of individuals with BA.2.2 infection were followed up. Using a log-binomial regression model in which the unvaccinated group as the control group, the risk ratios of different doses of inactivated vaccine in terms of preventing SARS-CoV-2 infection, symptoms of COVID-19, and pneumonia were calculated, and the protective effect of the vaccine was estimated. The Kruskal–Wallis rank-sum test was used to compare the effect of vaccination on the viral load of infected patients. From April to June 2022, a total of 2259 cohabiting close contacts of 1308 patients with SARS-CoV-2 infection aged ≥3 years were included. Of the included close contacts, 737 (32.63%) were positive for SARS-CoV-2 during the isolation period: 140 (19.00%) were infected but asymptomatic, 525 (71.23%) had mild infection, and 72 (9.77%) had pneumonia. There were no cases of severe or critical infection or death. The VE of the primary in preventing BA.2.2 infection, symptoms, and pneumonia was 37.35% (95% CI: 24.00–48.35), 42.36% (95% CI: 28.41–53.60), and 48.35% (95% CI: −5.34–74.67), respectively. The VE of the booster shot in preventing SARS-CoV-2 infection, symptoms, and pneumonia was 37.08% (95% CI: 24.29–47.70), 44.38% (95% CI: 31.45–54.87), and 61.46% (95% CI: 29.79–78.85), respectively. Six months after the booster vaccination, the VE of the booster in terms of preventing SARS-CoV-2 remained above 46%, and its VE in terms of the prevention of pneumonia remained above 72%. In the unvaccinated group, the Ct values of the N gene and ORFlab gene (represented by the median value and Q1 and Q3 in parentheses) were 26.45 (21.09, 31.61) and 28.06 (22.21, 32.06), respectively. There was no significant difference in the median value of either gene between the unvaccinated group, the partial group [25.81 (19.91, 31.78) and 26.98 (21.63, 31.17)], the primary group [28.79 (22.08, 32.34) and 29.30 (23.81, 33.86)], and the booster group [26.23 (21.66, 31.46) and 27.73 (23.38, 32.52)] (p > 0.05). Inactivated COVID-19 vaccines provided a certain level protection from infection and symptoms, very good protection against pneumonia, and it still has a modest protective effect at 6 months after vaccination. Booster doses are necessary to provide strongest protection. However, irrespective of their vaccination status, individuals with COVID-19 have a similar viral load.